The scientific view of the Holy Qur`an = نظرة علمية عن القرآن الكريم - Shogar, Ibrahim Adam Ahmed (Department of Qur'an and Sunnah Studies, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University, Malaysia, 2018)
This article investigates the Qur’anic approach on knowledge inquiry which emphasizes both the rational and empirical methods. It presents the various techniques adopted by the holy Qur´an to inculcate research interest and promote the scientific enterprise, such as inspiration and systemization of inquiry. Mankind needs to understand the world and explain its natural processes and historical events for various purposes. Human talent has been adopting various approaches to achieve this important goal, but it was unsuccessful in many cases. The foundation of modern science is grounded on the theory that observation and experimentation are the most reliable methods to uncover the truth of the world. Philosophers, however, emphasize the rational approach. They hold that the truth may manifest itself and it may be uncovered by means of investigation and removing the veil which may not be an easy task. However, once truth stands revealed before human intellect it has the power to see it and distinguish it from falsehood. It is the hypothesis of this article that the Qur’ānic approach on the natural and human phenomena plays an important role in integrating and synergizing the above two approaches. This claim is based on many factors, including the fact that the holy Qur´Én integrates different approaches with rational and empirical qualities to invite human attention for investigation. The holy Qur`an also, provides the epistemological and metaphysical principles that are useful for both methods of inquiry.